2002
DOI: 10.1073/pnas.052466499
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachiadensity and virulence attenuation after transfer into a novel host

Abstract: The factors that control replication rate of the intracellular bacterium Wolbachia pipientis in its insect hosts are unknown and difficult to explore, given the complex interaction of symbiont and host genotypes. Using a strain of Wolbachia that is known to over-replicate and shorten the lifespan of its Drosophila melanogaster host, we have tracked the evolution of replication control in both somatic and reproductive tissues in a novel host͞Wolbachia association. After transinfection (the transfer of a Wolbach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
268
1
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(299 citation statements)
references
References 33 publications
(30 reference statements)
13
268
1
9
Order By: Relevance
“…1). A similar effect was previously reported in newly transinfected Drosophila (22) and Ae. aegypti (6).…”
Section: Resultssupporting
confidence: 89%
“…1). A similar effect was previously reported in newly transinfected Drosophila (22) and Ae. aegypti (6).…”
Section: Resultssupporting
confidence: 89%
“…This assumption is corroborated by a number of studies on the bacterium Wolbachia. For example, it has been demonstrated that after transinfection of the Wolbachia strain popcorn from its native host Drosophila melanogaster to D. simulans, decrease of bacterial numbers in the ovaries over nine generations corresponded to increased fecundity of infected females (McGraw et al, 2002). The assumption is also supported by the observation that among the two CI-inducing Wolbachia strains that infect the mosquito Aedes albopictus, the one with the higher transmission rate is also the one with the higher bacterial density Dutton & Sinkins, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…Based on our data these strains clearly share a common ancestor, share identical wsp sequences [61], but can be discriminated by sampling dnaA and pdhB. All three strains are known to be CIinducers [9,24,36,37], and the wMelPop strain has also been shown to reduce the life span of its hosts, D.…”
Section: Recombination and Selectionmentioning
confidence: 85%